Effects of preoperative surgeon warm-up in video-assisted thoracoscopic surgery lobectomy - Enjie Wang; Jun Li; Tao Hong; Zexin Xie; Yong Ge; Xiaotong Zhou; Hao Zhang (BMC Surgery, 2024)
Abstract Background In various surgical specialties, preoperative surgical warm-up has been demonstrated to affect a surgeon’s performance and the perioperative outcomes for patients. However, the influence of warm-up activities on video-assisted thoracoscopic surgery lobectomy (VATSL) remains largely unexplored. This study aims to investigate the potential effects of preoperative surgical warm-up on VATSL. Methods A cohort of 364 patients diagnosed with lung cancer through pathology and undergoing VATSL at the Thoracic Surgery Department of Xuzhou Medical University from January 2018 to September 2022 were included. Patients were categorized into two groups: the warm-up group, comprising 172 patients undergoing their first VATSL of the day, and the warm-up effect group, consisting of 192 patients undergoing their second VATSL on the same day. Propensity score matching was employed to compare operation times and postoperative complications between the two groups, resulting in 159 matched cases in each group. Results There were no statistically significant differences in operation time (154.5 ± 54.9 vs. 147.2 ± 54.4 min, p = 0.239) and postoperative complications (including pulmonary infection, atelectasis, long-term pulmonary air leakage requiring incision suture in the operating room, and postoperative pleural effusion) (14:22 cases, p = 0.157) between the warm-up and warm-up effect groups. Conclusion The findings suggest that preoperative surgical warm-up does not significantly affect the perioperative outcomes of VATSL.